Estimates of the initial impact of the COVID-19 epidemic on overall mortality: evidence from Italy - Conti, Sara (ERJ Open Res, 2020)
This study provides evidence of the enormous death toll attributable to COVID-19 https://bit.ly/2X4C6a8